Calcium oxalate deposition on cotton fabric in the presence of different anionic surfactants. Issue 11 (31st August 2021) - Li, Chen; Wang, Lijie; Xu, Hong; Dong, Jinxiang
Abstract: Sodium oxalate is a detergent builder candidate due to its good performance in detergent formulations. However, sodium oxalate softens water by forming precipitates, thus preventing calcium oxalates from depositing on fabrics is a key goal for sodium oxalate-based detergents. Surfactants and builders are two main ingredients in detergents. Here, six anionic surfactants were chosen to study their deposition effects on cotton fabric during washing. Ash deposition analysis was used to evaluate the amount of calcium oxalate deposition on cotton fabric. X-ray diffractometer and scan electron microscope were performed to the study crystal phase and morphological changes of calcium oxalates in the presence of the different anionic surfactants, and the total interaction energy between calcium oxalates and cotton fabric was calculated by Derjaguin–Landau–Verwey–Overbeek (DLVO) theory in each case. The results showed that different anionic surfactants have a different effect on the ash deposition, primarily that the concentration of surfactants had less influence on the deposition with the exceptions of sodium dodecyl benzene sulfonates (SDBS) and sodium methyl ester sulfonates (MES). Anionic surfactants can influence both phase and morphology of calcium oxalates, which might influence the zeta potential of the calcium oxalates. When the calcium oxalates are of the same phase, the deposition amount decreased with increasing maximum total interaction energy (VTmax ). The greatest decrease in calcium oxalates deposition occurred in the presence of sodium alkyl ether sulfates (AES) and disodium lauryl sulfosuccinates (AEMES), of which VTmax is the largest. Graphical Abstract: Abstract : UF0001